1979
DOI: 10.1111/j.1365-2265.1979.tb03043.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience With Human Growth Hormone in Great Britain: The Report of the MRC Working Party

Abstract: The Working Party on human growth hormone (hGH) has during the past decade developed a system for the evaluation and treatment of patients suffering from hGH lack. Today there are nineteen measurement centres in the United Kingdom at which patients are assessed and where the effects of therapy are monitored. The current supply of hGH, which is prepared from pituitary glands collected by pathologists in the National Health Service, is just enough to meet demand, but research conducted on behalf of the Working P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 26 publications
10
66
2
Order By: Relevance
“…Moreover, 12 out of 16 patients (75%) increased their growth velocity more than 2 cm/year, and the adult height prediction was also improved (mean increase of 0.5 SDS). These findings, even though they are in agreement with those reached by other authors in the treatment of this syn drome [1,[5][6][7] are similar to those observed in short stature, but normal GH secretion in patients with etiolo gies different from GHND [17][18][19][20][21] is clearly lower than that observed in the treatment of growth failure due to classical GH deficiency (GHD) with the same, or even lower, therapeutic regimen [13][14][15][16].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, 12 out of 16 patients (75%) increased their growth velocity more than 2 cm/year, and the adult height prediction was also improved (mean increase of 0.5 SDS). These findings, even though they are in agreement with those reached by other authors in the treatment of this syn drome [1,[5][6][7] are similar to those observed in short stature, but normal GH secretion in patients with etiolo gies different from GHND [17][18][19][20][21] is clearly lower than that observed in the treatment of growth failure due to classical GH deficiency (GHD) with the same, or even lower, therapeutic regimen [13][14][15][16].…”
Section: Discussionsupporting
confidence: 79%
“…in the release of pituitary GH secondary to abnormalities in neurotransmitter path ways which may result in decreased GHRH and/or increased somatostatin secretion [1,12]; however, at the present time, the etiology underlying this disorder still remains unknown, and an adequate therapeutic regimen has not been established yet. In this sense, although the dosage used here may be considered as a low dosage, it is within the range of that habitually employed in growth failure treatment due to GH deficiency, and it has widely been demonstrated to be effective [13][14][15][16], and, in fact, is one of the most common dosages used by pediatric endocrinologists.…”
Section: Discussionmentioning
confidence: 99%
“…Because catch-up growth after GH replacement therapy is greatest during the first 2 years, 11,12 we set the cut-off between the short-and long-term therapy groups as 2 years of GH therapy.…”
Section: Methodsmentioning
confidence: 99%
“…criteria before entry into the study and have: (1) a growth velocity standard deviation score between 0 and -0-8 in the first year of the study; (2) skeletal age less than 10 years; (3) 28-2 (9-1) mU/l in the control group). Children in the control group were slightly taller, but height velocities were identical in the two groups.…”
Section: Introductionmentioning
confidence: 99%